All my secrets [large type] - Austin, Lynn N. (Austin, Lynn N. Gilded age, 2024)
"New York, 1898. The only thing more shocking than Arthur Stanhope III's unexpected death is the revelation that his will bestows his company -- and most of the vast fortune that goes with it -- to the nearest male heir, leaving his mother, wife, and daughter nearly impoverished. His widow, Sylvia, quickly realizes she must set aside her grief to ensure their daughter, Adelaide, is launched into society as soon as the appropriate mourning period passes. If Sylvia can find a wealthy husband for Addy before anyone realizes they're practically destitute, there will be little disruption to the lifestyle they're accustomed to. Sylvia's mother-in-law, Junietta, believes their life could use a little disruption. She has watched Sylvia play her role as a society wife, as Junietta once did, despite what it cost them both. Junietta vows to give her granddaughter the power to choose a path beyond what society expects. But for Addy to have that chance, both mother and grandmother must first confront painful truths about their own choices. Only in bringing their secrets to light can they hope to reshape their family inheritance into a legacy more fulfilling than they ever dared dream."--